A facile route to prepare reflective counter electrode for enhanced dye-sensitised solar cell efficiency. (2016) - Li, Luping; Xu, Cheng; Zhao, Yang; Ziegler, Kirk J.
Dye sensitised solar cells (DSSCs) represent a promising technology for the development of next-generation photovoltaics. The counter electrode in a DSSC typically consists of a tin-doped indium oxide (ITO) substrate covered by Pt as the catalyst. To increase DSSC efficiency and reduce fabrication cost, most existing methods involve multiple steps and are time consuming. In this work, we present a facile and low-cost alternative to prepare reflective counter electrodes for DSSCs with high efficiency. By simply sputtering a 30-nm-thick Pt film on ITO without further treatment, cell efficiency reached 7.08%, corresponding to an 11% increase from the control. Similar efficiency was achieved when a Pt film was sputtered on regular glass, which is a low-cost alternative to ITO. UV-vis spectroscopy showed that the reflectance for the control was below 30%, while the reflectance for the Pt-sputtered counter electrodes was above 70%, which is higher than the counter electrodes prepared by other methods.